IMF radial gradients in most massive early-type galaxies - La Barbera, Francesco; Pasquali, Anna (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Using new long-slit spectroscopy obtained with X-Shooter at ESO-VLT, we study, for the first time, radial gradients of optical and near-infrared init
Gesehen am 08.10.2019